Sceening and identification of pregnancy associated glycoprotein (PAG) and other protein related to early stage of pregnancy in goat - Noor Syaheera Ibrahim
The study was conducted to detect the presence of pregnancy associated glycoprotein (PAG) in the serum of Shami (Damascus) goats. Besides PAG, other proteins associated with goat's pregnancy were also screened using proteomic approach. Sampling was carried out at the National Veterinary Institute of Biodiversity (IBVK), Jerantut, Pahang where blood samples were taken every two weeks for analysis. SDS-PAGE analysis showed there was no difference observed in protein separation when the sample of day 0, day 14 and day 28 were compared. Thus, the serum samples were further analyzed using several proteomics approaches. Using proteomic techniques, the proteome map of non-pregnant Shami goat serum could be established, which was then used in comparison with the pregnant serum during the gestation period. The serum samples of day 0, 14 and 28 of pregnancy were subjected to two dimensional gel electrophoresis where the proteins were separated based on their molecular weight and pl. The proteome maps were the analyzed using Image Master 2 D Platinum Software (version 7) in order to detect any differentially expressed proteins. Based on the Image Master analysis, there were five spot proteins (spot 196, 51, 223 and 95) which significantly expressed in day 14. Therefore, these spot proteins were analyzed using Maldi-Tof/Tof analysis for protein identification. From the Maldi-Tof/Tof result, the spot 196 and 51 were identified as albumin precursors,spot 223 zinc-alpha-2-glycoprotein precursor spot 239 as immunoglobulin lambda light chain and spot 95 as serum albumin precursor. According to the previous reports, MW and pl of albumin spot was comparable to that of pregnancy-associated glycoprotein (PAG). Therefore, PAG was expected to be overlapped with albumin. Liquid-chromatography tandem mass spectrometry was later used in order to detect and identify the proteins contained in albumin spot. Out of 11 proteins, pregnancy-associated glycoprotein-1 was successfully detected. Futhermore, immunoblotting was employed to validate LC-MS/MS result. From the result, molecular weight and pl of Damascus goat PAG-1 were comparable with other species' placenta PAG.